Native fruits of peru as a potential source of nutrients, bioactive compounds and antioxidant capacity in the nutritional requirements of vulnerable groups - La Rosa A.J.O. (2021)
The authors thank the National Fund for Scientific and Technological Development (FONDECYT) of Lima, Peru, for the support provided and the Graduate School of the National University Federico Villarreal for the facilities provided for the completion of this study.